Clinically Integrated Physical Therapist Practice in Cancer Care: A New Comprehensive Approach. Issue 3 (10th February 2020) - Barnes, Christopher A; Stout, Nicole L; Varghese, Jr, Thomas K; Ulrich, Cornelia M; Couriel, Daniel R; Lee, Catherine J; Noren, Christopher S; LaStayo, Paul C
Abstract: Best practice recommendations in cancer care increasingly call for integrated rehabilitation services to address physical impairments and disability. These recommendations have languished primarily due to a lack of pragmatic, generalizable intervention models. This perspective paper proposes a clinically integrated physical therapist (CI-PT) model that enables flexible and scalable services for screening, triage, and intervention addressing functional mobility. The model is based on (1) a CI-PT embedded in cancer care provider clinics, and (2) rehabilitation across the care continuum determined by the patient's level of functional mobility. The CI-PT model includes regular screening of functional mobility in provider clinics via a patient-reported mobility measure—the Activity Measure for Post-Acute Care, a brief physical therapy evaluation tailored to the specific functional needs of the individual—and a tailored, skilled physical therapist intervention based on functional level. The CI-PT model provides a pragmatic, barrier-free, patient-centric, data-driven approach to integrating rehabilitation as part of standard care for survivors of cancer. The model standardizes CI-PT practice and may be sufficiently agile to provide targeted interventions in widely varying cancer settings and populations. Therefore, it may be ideal for wide implementation among outpatient oncological settings. Implementation of this model requires a shared approach to care that includes physical therapists, rehabilitation administrators, cancer care providers, and cancer center administrators.